Strategies of Survival and Resilience: Psychological Dynamics of Cancer Survivors in Indonesian Navy - Lufta, Navthan; Jaro'ah, Siti; Harita, Adiwignya Nugraha Widi; Setiawan, Eko (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2025)
This study aims to explore the psychological dynamics and identify the relationships between survival-resistance strategies, social support, and resilience among Indonesian Navy cancer survivors. A mixed-methods sequential exploratory design was adopted by combining in-depth interviews of 3 participants with quantitative surveys of 36 respondents. The qualitative analysis identified five critical phases in psychological trajectory which were symptom avoidance behavior and denial, multidimensional psychological distress (anxiety, body image disruption, spiritual disappointment), intra-individual mitigation through religiosity and cognitive reappraisal, amplification by family and institutional support, and resilience outcomes manifesting as tranquility and post-traumatic growth.The quantitative results showed substantial correlations between social support and resilience (r=0.894; p<0.001), social support and coping strategies (r=0.932; p<0.001), as well as coping strategies and resilience (r=0.839; p<0.001). The methodological triangulation confirmed that resilience was a synergistic product of intra-individual capacities and social ecology rather than an isolated dispositional attribute.